Palestina-Israel Conflict: Two-State Solution and Human Rights Advocacy in the Palestine-Israel Conflict, and Indonesia's Position as Security Council - Saputra Husein Siregar; Muslim Pohan; Hanizar Meda Simbolon (Spiritus: Religious Studies and Education Journal, 2024)
The Israeli-Palestinian conflict is a very sensitive discussion and full of complex problems, where this conflict has led to a high humanitarian crisis that requires international action to seek peace in the region. Of course, the peace efforts that are being made are not as simple as turning the palm of one's hand. So in this research/writing, the author tries to explain the Israeli-Palestinian conflict, what kind of humanitarian crisis that occurs without any maximum action from the international community, as well as what kind of peaceful efforts in realizing an independent and sovereign state for the Palestinian people and what the role of the Indonesian state is to fully support the independent state of Palestine. In this type of research, the author uses descriptive qualitative methods. Where she tries to understand in general the data to be analysed. Data processing uses Huberman's theory by reducing the data collected, analyzing the data, and drawing conclusions or verifying the data (Reduction, Analysis, and Conclusion Drawing or Verification). In this writing, a library research approach is used by searching and collecting data in the form of documents related to the topic of this discussion as a reinforcement for writing this article. The results of this study indicate that in the Israeli-Palestinian conflict, there are human rights violations in the form of indiscriminate attacks by Israeli soldiers in Palestine, the need to seek a peaceful solution with the establishment of an independent Palestinian state with the concept of a two-state solution, and the role of Indonesia in playing an active role in achieving world peace.